Ảrts and handicrafts of Vietnam / Nguyễn Khắc Viện, Lê Huy Vân - Nguyễn, Khắc, Viện
This book is published with the aim of introducing readers to the main features, origins and historical development of the arts and handicrafts of Vietnam, together with some current issues. We trust it will be of use to all those wishing to undertake research on and become involved in co-operation with Vietnam.